The Effectivness of Problem Based Learning Teaching Model to Increase Students’ Rational Thinking Skills - Khaerus Syahidi; Fartina Fartina (Jurnal Pembelajaran Fisika, 2020)
Problem Based Learning is learning that is delivered by presenting a problem, asking questions, facilitating investigation, and opening dialogue. This study aims to determine the effect and effectiveness of PBL learning models on students' rational thinking skills and students’ responses to the learning process applied. The research design used was one group of time-series designs. The population of the study was all students of XI Science class MA Hubbul Jiron NW Pringgarta, while the samples were 21 students of XI Science class in the MA. The Problem Based Learning (PBL) learning model was applied to the sample class by three learning series that began with a pretest and ended with a posttest. Students' rational thinking skills are measured using a test in the form of multiple-choice questions with 23 items that have been validated and tested. The effectiveness of the Problem Based Learning model in improving students’ rational thinking skills is obtained through normalized gain analysis of pretest and posttest scores. The results of the study showed that the PBL learning model is effective to improve students' rational thinking skills with the average normal gain values (N-gain) is 0.57, and questionnaire analysis showed 97% of students enjoyed PBL learning. Students are highly motivated to participate actively in the learning process.Keywords: Problem Based Learning, Rational Thinking Skills DOI: http://dx.doi.org/10.23960/jpf.v8.n1.202009